Fast HPLC-DAD Method for Estimation of Catechin for Standardization of Extracts and Antiasthmatic Polyherbal Formulations Containing Albizia lebbeck - Desai, Sonal; Tatke, Pratima; Gaitonde, Vinay; Gabhe, Satish (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Many marketed polyherbal formulations containing Albizia lebbeck are available for treatment of allergic disorders such as asthma and bronchitis. But these formulations are not standardized in terms of markers. The present work discusses development and validation of a new, simple and rapid HPLC-DAD method for quantification of phytomarker- catechin in methanol extracts for standardization of extracts and polyherbal formulations containing Albizia lebbeck. Materials and Methods: HPLC analysis was carried out using C18 column (100 mm X 4.6 mm, 2.6 μm). 0.1% Phosphoric acid and acetonitrile in gradient mode was used as mobile phase. The column oven was equilibrated at 28°C. The injection volume was 2 μl and detection was carried out at 279 nm. Results: The developed HPLC method was found to be linear over the range of 3.0-60 μg/ml with correlation coefficient of 0.9998. The LOD and LOQ were found to be 1.0 μg/ml and 3.0 μg/ml, respectively. The recovery of the catechin was between 97.12 % -100.04 %. The low RSD values of intra and inter-day precision studies indicated good precision of the developed method. The method was found to be robust as small changes in method parameters did not significantly change peak symmetry and content of catechin. Conclusion: The developed method was sensitive, rapid and requires no special technique for sample preparation. The method was successfully applied for standardization of three bark extracts and marketed polyherbal formulations containing Albizia lebbeck.
Keywords: Albizia lebbeck; Catechin; Fabaceae; HPLC; Shirish